STOCK RETURNS: EFFECT OF RETURN ON ASSETS, RETURN ON EQUITY, DEBT TO EQUITY RATIO, AND DIVIDEND PAYOUT RATIO - Gilang Danendra Caesaro; Christina Heti Tri Rahmawati; Lukas Purwoto (MANAJEMEN DEWANTARA, 2023)
Maximum stock returns from investment value will be obtained if investors have insight and information, one of which is fundamental analysis using financial ratios, so that it can be used as a guide in making the right investment decisions in the capital market. The financial ratios used in this research include profitability ratios as measured by Return on Assets (ROA) and Return on Equity (ROE); solvency ratio as measured by the Debt to Equity Ratio (DER); and the valuation ratio as measured by the Dividend Payout Ratio (DPR). The purpose of this research is to determine the effect of ROA, ROE, DER, and DPR on stock returns of LO45 companies. This research uses a population of 62 LQ45 companies. The sample for this research was 44 LQ45companies. The sampling technique used was purposive sampling with the criteria of LQ45 companies that published complete financial reports and distributed dividends regularly from 2015 to 2020. The data collection technique used panel data. The data analysis technique used was multiple linear regression analysis with the SPSS 25 application. The research results showed that ROE and DPR had a positive effect on stock returns, while ROA and DER had no effect on stock returns. The implication of the results of this research is that it is hoped that investors can make the right investment decisions to buy or sell shares and allocate their assets to the LQ45 company, so as to get optimal stock returns Keywords: Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR), Stock Returns